2009
DOI: 10.1105/tpc.108.065243
|View full text |Cite
|
Sign up to set email alerts
|

Hunting for Plant Nitric Oxide Synthase Provides New Evidence of a Central Role for Plastids in Nitric Oxide Metabolism

Abstract: Nitric oxide (NO) has emerged as a central signaling molecule in plants and animals. However, the long search for a plant NO synthase (NOS) enzyme has only encountered false leads. The first works describing a pathogen-induced NOS-like plant protein were soon retracted. New hope came from the identification of NOS1, an Arabidopsis thaliana protein with an atypical NOS activity that was found to be targeted to mitochondria in roots. Although concerns about the NO-producing activity of this protein were raised (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
113
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(121 citation statements)
references
References 60 publications
2
113
0
3
Order By: Relevance
“…However, recent evidence shows that AtNOA1 localizes in chloroplast (Flores-Pérez et al, 2008;Gas et al, 2009). Organelle localization of AtNOA1 suggests that activation of this protein requires signal transduction from extracellular stimuli to intracellular organelle.…”
Section: No Plays An Important Role In Extcam Guard Cell Signalingmentioning
confidence: 99%
“…However, recent evidence shows that AtNOA1 localizes in chloroplast (Flores-Pérez et al, 2008;Gas et al, 2009). Organelle localization of AtNOA1 suggests that activation of this protein requires signal transduction from extracellular stimuli to intracellular organelle.…”
Section: No Plays An Important Role In Extcam Guard Cell Signalingmentioning
confidence: 99%
“…Unlike animal systems, knowledge of NO generation and subcellular location in plants remains largely elusive, and the data are sometimes contradictory and ambiguous (Zemojtel et al, 2006;Jasid et al, 2006;Gas et al, 2009). In previous studies, we detected L-Arg-dependent nitric oxide synthase (NOS) activity in isolated pea (Pisum sativum) leaf peroxisomes .…”
mentioning
confidence: 99%
“…The results suggest that there may be a common mechanism for NO production in time and space in tobacco. Recent studies suggest that plastids play a central role for NO metabolism by investigating NOS (Gas et al 2009), and in several plant tissues and purified organelles, including mitochondria, the nucleus, and peroxisome, NOS-like activities have been (Barroso et al 1999;Corpas et al 2006;Tian et al 2007). Why NO was produced in these places is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…NO can be synthesized in plant by different routes, both enzymatically and nonenzymatically (Arisan et al 2009). Most work focuses on NOS-like enzyme (Gas et al 2009) and NR (Yamasaki and Sakihama 2000). Recent studies found that polyamine induced rapid biosynthesis of NO in Arabidopsis thaliana (Tun et al 2006;Yamasaki and Cohen 2006), suggesting there maybe a possible linkage between polyamine and nitric oxide.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%